The Action Mode: Mile 22 and the Tension of Hypermediated Embodiment - Jonah Jeng (Film-Philosophy)
This article contends that, despite the naturalization of hypermediacy in everyday life, a tension persists between the proliferation of digital media and human phenomenal experience. Everyday phenomenal experience, in its delineation of a unified spatial field populated with bounded physical objects, exists in palpable tension with the subperceptual digital networks and data flows that underpin contemporary society and are indexed by aesthetics of hypermediacy. I contend that cinema, which simultaneously appeals to phenomenal experience and has itself become permeated by hypermediacy and the related aesthetic tendency of post-continuity, is a key site for expressing this larger cultural tension. Furthermore, I propose that what I am calling the action mode – action cinema’s anxious articulation of the physical body’s limits and capacities – is ideally suited to making this tension not only seen but felt. The film Mile 22 (Peter Berg, 2018), by combining the action mode with an aesthetic and thematic exploration of extreme hypermediacy, exemplifies the action mode’s potential in this way.